Cardiovascular risks among shift and non-shift workers in a public medical centre in Kuala Lumpur - Moy, Foong Ming; Hoe, V.C.W.; Tan, C.P.L.; Rosmawati, M. (Faculty of Medicine, University of Malaya, 2010)
Night work and rotating shift work are found to be detrimental to the health of workers. A cross sectional analytical study was conducted among the employees of a public medical centre in Kuala Lumpur. A total of 380 employees participated in the health screening and questionnaire survey. The majority of the respondents were Malays, females, and with mean age of 49 years old. The shift workers persistently had higher but non-significant proportions of being overweight/obesity and unhealthy clinical indicators such as systolic and diastolic blood pressure, fasting blood glucose and lipid profile except waist circumferences and HDL-cholesterol. There were also slightly more shift workers diagnosed with diabetes mellitus, hypertension or coronary heart disease (p>0.05). Although the present study could not provide established evidence for a relationship between shift work and cardiovascular risks, this could serve as a pilot study for future studies in this area.